2008
DOI: 10.2334/josnusd.50.151
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 and tumor necrosis factor-α gene polymorphisms in Turkish patients with localized aggressive periodontitis

Abstract: Localized aggressive periodontitis (LAgP) is a complex multifactorial periodontal disease to which genetic factors are thought to predispose individuals. Interleukin-1 (IL-1) and tumor necrosis factor-alpha (TNF-alpha) are potent immunomodulators and proinflammatory cytokines that have been implicated in the pathogenesis of autoimmune and infectious diseases and proposed to be risk factors for LAgP. Our aim was to investigate IL-1 alpha (+4845), IL-1 beta (+3954), and TNF-alpha (-308) gene polymorphisms in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
2
17

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 52 publications
3
37
2
17
Order By: Relevance
“…Studies on periodontal disease have revealed a genetic basis; however, the specific nature of the genetic risk remains unclear. 17 Cytokines play a key role in the regulation of the immune response. The maximal capacity of cytokine production varies among individuals and correlates with polymorphisms in the cytokine gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on periodontal disease have revealed a genetic basis; however, the specific nature of the genetic risk remains unclear. 17 Cytokines play a key role in the regulation of the immune response. The maximal capacity of cytokine production varies among individuals and correlates with polymorphisms in the cytokine gene promoters.…”
Section: Discussionmentioning
confidence: 99%
“…Another researchers found that the majority of the sample was female, and also found men and women have the same representation in these disorders. 7,13 Many studies conducted to examine the role of gene polymorphisms on the host response of patients with periodontitis. Gene polymorphisms that occur in patients with periodontitis are likely to affect protein expression they produce, and will ultimately change the cell morphology and function affecting innate and adaptive immune responses, and possibly manifested in the clinical condition of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Cytokines, Interleukin-1, is a pro-inflammatory protein with cytokine functions, such as as chemotactic factors playing a role in the onset of inflammatory, and as a mediator and regulator of inflammatory responses in the host innate immune system which plays in a number of biological activities, including proliferation, homeostasis, regeneration, reparation and inflammation. 6,7 Biological effects of IL-1 depend on the number of cytokines that are released at low levels with their main function as local inflammatory mediators. Meanwhile, IL-1 at high levels moves into circulation, and invited endocrine effects.…”
Section: Introductionmentioning
confidence: 99%
“…There are two types of periodontitis disease, namely aggressive (localized and generalized) and chronic, both of which involve loss of supporting structures of the teeth (5). Aggressive periodontitis is characterized by fast rates of progression, tissue attachment-loss and tissue destruction (6). Due to its increasing prevalence worldwide, aggressive periodontitis is regarded as a major health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Periodontal disease was diagnosed according to clinical and radiographic parameters that included bleeding on probing, probing pocket depth and clinical attachment loss. Aggressive periodontitis was defined by inter-proximal attachment loss affecting at least three teeth that were either first molars or incisors (3,6,25). For the patient and control groups, the exclusion criteria were a history of HIV and/or hepatitis infection, diabetes, usage of anti-inflammatory and/or immunosuppressive drugs, pregnancy or lactation, and smoking.…”
Section: Introductionmentioning
confidence: 99%